Provoked venous thromboembolism during ten-year follow up at the Clinical Centre University of Sarajevo - Akif Mlačo; Nejra Mlačo; Demir Bejtović; Muhamed Spužić; Alen Džubur; Edin Begić (Medicinski glasnik, 2019)
Aim: To determine risk factors for deep vein thrombosis (DVT) in hospitalized patients in a 10-year follow-up. Methods: In this observational study data were collected from the disease history of patients admitted to the Department of Angiology of the Clinical Centre University of Sarajevo in the period of 10 years (2008-2017). Of 6246 hospitalized patients, 1154 were with established diagnosis of DVT and included in the study as a basic inclusion criterion. Results: Provoked venous thromboembolism was recorded in 45.75% of hospitalized patients. In 54.25% cases DVT was classified as idiopathic; in the remaining cases with DVT external risk factors were identified. Every fourth patient had a history of malignancy, and this risk factor was significantly more common among women and younger patients. Cancer of female reproductive organs, colon, lung, breast and prostate cancer were most common. One of 10 women had DVT during pregnancy or postpartum period. Out of the total number, 10.9% patients had DVT after surgery, 2.3% after injury. DVT was found in 1.6% of drug addicts. Rethrombosis was diagnosed in 5.2% patients within a year, while 9.2 % patients had rethrombosis within five years. Conclusion: Provoked venous thromboembolism is an entity that can be prevented. Malignancy and surgical treatment are the most common risk factors and these patients should be treated with special care. The creation of a register of patients with venous thromboembolism in Bosnia and Herzegovina would enable the development of a preventive strategy in the groups of patients at risk.
Keywords: risk factors; thrombosis; treatment